2013
DOI: 10.6028/nist.tn.1785
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of SelfContained Breathing Apparatus Facepiece Lenses Exposed to Radiant Heat Flux

Abstract: Fire fighters are exposed to highly variable thermal environments including elevated temperatures, convective heat flux, and radiant heat flux, which can put a significant burden on personal protective equipment. Thermally degraded and melted self-contained breathing apparatus (SCBA) facepieces have been identified as a contributing factor in certain fire fighter fatalities and injuries in the United States. At the current time, standard performance tests for SCBA facepieces are conducted at less severe therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…It has been reported that surface cracking of a firefighter's SCBA facepiece can begin to occur at temperatures around 180°C and at an exposure to a heat flux of 5 kW/m 2 for a minimum of 12 min [35]. Firefighter radios begin to experience performance problems (drift of signal frequency, failure to transmit, etc.)…”
Section: Fire Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that surface cracking of a firefighter's SCBA facepiece can begin to occur at temperatures around 180°C and at an exposure to a heat flux of 5 kW/m 2 for a minimum of 12 min [35]. Firefighter radios begin to experience performance problems (drift of signal frequency, failure to transmit, etc.)…”
Section: Fire Technologymentioning
confidence: 99%
“…According to Putorti et al, an SCBA facepiece can begin to bubble when exposed to a heat flux of 5 kW/m 2 for approximately 12 min or 7 kW/m 2 for 6 min [35]. During Exposure 1, bubbling of the facepiece began to occur after roughly 9 min of Class I and Class II heat flux exposures (average of 1.1 kW/m 2 ) followed by less than 9 min of Class III heat flux exposures containing an average of 5.0 kW/m 2 .…”
Section: Fire Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, exposures below these levels -that may result in structural changes to the lens yet provide minimal visual indications of damagewere not studied. In their conclusions, Putorti et al suggested that "Although much was learned about conditions associated with thermal degradation of SCBA facepiece lenses, more research and development are needed to understand the thermal degradation of facepiece lenses" [21].…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…To follow up these experiments, NIST developed a laboratory based radiant heat exposure protocol for testing SCBA facepieces [21]. Putorti et al conducted a series of laboratory experiments, which examined the thermal performance of polycarbonate SCBA facepieces under a variety of radiant heat flux levels, with a focus on severe conditions where lens degradation and/or failure may occur on the order of 10 minutes.…”
Section: Current State Of Knowledgementioning
confidence: 99%